Feelings of insecurity regarding organized crime in Tamaulipas, Mexico - Ariagor Manuel Almanza-Avendaño; Martha Patricia Romero-Mendoza; Anel Hortensia Gómez-San Luis (Instituto Nacional de Salud Pública, 2018)
Objective. To understand the meanings, feelings and practices associated with insecurity in a context with the presence of organized crime. Materials and methods. The study was conducted in a municipality of Tamaulipas, México, with high levels of violence. Semi-structured interviews were conducted with a purposive sample of thirty indirect victims. Interview transcriptions underwent computer-assisted qualitative analysis using the MAXQDA program. Results. Threatening situations and perceived causes of insecurity in the local context were identified. Various psychosocial consequences of insecurity and coping strategies are also described. Conclusions. Although the strategies used attempt to reduce the impact of insecurity on mental health, a transformation of mobility in public space and social relations is observed. Citizens handle insecurity at the individual level, even when it is attributed to structural causes.